Coccidioidomycosis and the skin: a comprehensive review - García García, Sandra Cecilia; Salas Alanís, Julio César; Flores, Minerva Gomez; González González, Sergio Eduardo; Vera Cabrera, Lucio; Ocampo Candiani, Jorge (2015)
Coccidioidomycosis is a highly prevalent disease in the Western hemisphere. It is considered one of the most virulent primary fungal infections. Coccidioides species live in arid and semi-arid regions, causing mainly pulmonary infection through inhalation of arthroconidia although many other organs can be affected. Primary inoculation is rare. Since the first case of coccidioidomycosis was reported in 1892, the skin has been identified as an important target of this disease. Knowledge of cutaneous clinical forms of this infection is important and very useful for establishing prompt diagnosis and treatment. The purpose of this article is to provide a review of this infection, emphasizing its cutaneous manifestations, diagnostic methods and current treatment.